UPAYA MENINGKATKAN MINAT BELAJAR SISWA PADA PEMBELAJARAN BAHASA INDONESIA DENGAN MENGGUNAKAN MODEL DIRECT LEARNING PADA SISWA KELAS V - Rara Marselina Jupon; Leni Anggraeni; Ponidi Ponidi (Universitas Sarjanawiyata Tamansiswa, 2020)
The low interest of students in Indonesian language subject caused the majority of the students to be less enthusiastic about the lessons delivered by the teacher, so that students’ learning outcomes were low. The purpose of this study was to increase students’ interest and learning outcomes in Indonesian subjects through direct learning for 5th grade students in SDN 3 Karangraja. The subjects of this study were the fifth-grade students of SDN 3 Karangraja, with the total of 25 students. This research was conducted for two cycles. The results showed that in each cycle there was a progress that was proven with the result in the first cycle, the students’ interest reached 13 students (52.00%) in learning and students who passed the learning through the improvement in cycle I were only 13 students (52.0%). In the second cycle improvement, there was an increase in interest of 23 students (92.00%). Thus, the learning outcomes of students were increasing with the number of 23 students (92.0%) passed the subject. This result proved that through the direct learning method students could solve their own problems in Indonesian language subject.